2018
DOI: 10.1063/1.5045868
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory electrospun nonwovens based on crosslinked poly(ε-caprolactone) for multifunctional biological applications

Abstract: In this work we have explored the capabilities of an electrospun mat, realized in crosslinked poly(εcaprolactone), to be employed as a scaffold for specific biological applications. Its shape memory behavior was here exploited to easily control fiber orientation and to guide cellular alignment. Randomly oriented mats were transformed in a stable shape with various degrees of fiber alignment by simply varying the maximum strain applied throughout proper thermo-mechanical cycles. The effect of fiber alignment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Biocompatible scaffolds can be designed to promote the repair of the tissue in different manners starting from providing a physical support for the development and proliferation of the cells and finishing to the direct guidance of the cells growth (Ginestra et al, 2017b(Ginestra et al, , 2017c. Artificial scaffolds consisting of nanofibers have large surface area and high porosity suitable to assure cells attachment and adhesion, showing that electrospinning is a potential strategy to produce biomimetic scaffolds (Ginestra et al, 2016a;Inverardi et al, 2018). The scaffolds produced by electrospinning are characterized by a 3D fibrous architecture and interconnected porosity that make them a suitable option for the neural tissue engineering (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatible scaffolds can be designed to promote the repair of the tissue in different manners starting from providing a physical support for the development and proliferation of the cells and finishing to the direct guidance of the cells growth (Ginestra et al, 2017b(Ginestra et al, , 2017c. Artificial scaffolds consisting of nanofibers have large surface area and high porosity suitable to assure cells attachment and adhesion, showing that electrospinning is a potential strategy to produce biomimetic scaffolds (Ginestra et al, 2016a;Inverardi et al, 2018). The scaffolds produced by electrospinning are characterized by a 3D fibrous architecture and interconnected porosity that make them a suitable option for the neural tissue engineering (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Inverardi et al [139] produced another scaffold based on crosslinked PCL, and instead of changing the microstructure by modifying the electrospinning set-up [140], they took advantage of its SM behavior in modulating the fiber alignment by fixing different temporary shapes with different microstructures. The material is able to fix and recover the temporary and permanent shapes even when high deformation was applied (100%).…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…A limited number of studies reported the possibility to obtain high aligned fibers by the modification of the collector geometry (Li et al , 2003; Li et al , 2004) or the optimization of the melt ES writing process (Wunner et al , 2018). To improve the deficiency of mechanical properties of electrospun fibers, several studies have demonstrated various blending systems, process parameters designs, and post-processing treatments (Inverardi et al , 2018). Furthermore, elctrospinning has been modified or combined with various other fabrication methods (Castells-Sala et al , 2013; Ginestra et al , 2017a; Ginestra et al , 2016).…”
Section: Introductionmentioning
confidence: 99%